2020
DOI: 10.1111/cns.13370
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal neural crest stem cell transplantation as a promising therapeutic strategy for ischemic stroke

Abstract: IntroductionCell‐based therapy is considered as promising strategy to cure stroke. However, employing appropriate type of stem cell to fulfill many therapeutic needs of cerebral ischemia is still challenging. In this regard, the current study was designed to elucidate therapeutic potential of epidermal neural crest stem cells (EPI‐NCSCs) compared to bone marrow mesenchymal stem cells (BM‐MSCs) in rat model of ischemic stroke.MethodsIschemic stroke was induced by middle cerebral artery occlusion (MCAO) for 45 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…This striking data supports the beneficial function of these grafted stem cells in damaged tissues. Furthermore, EPI-NCSCs showed superior immunomodulation properties in animal models of nerve injury and stroke, as they upregulated the anti-inflammatory cytokines, whilst reducing the expression of pro-inflammatory cytokines [34,124,125]. Since EPI-NCSCs can easily be transduced to overexpress GFP [126], genetic manipulations to elevate neurotrophic factor expression seems feasible, and with this review we hope to prompt further studies investigating the beneficial characteristics of those cells.…”
Section: Epidermal Neural Crest Stem Cells As a Promising Candidate Imentioning
confidence: 98%
See 3 more Smart Citations
“…This striking data supports the beneficial function of these grafted stem cells in damaged tissues. Furthermore, EPI-NCSCs showed superior immunomodulation properties in animal models of nerve injury and stroke, as they upregulated the anti-inflammatory cytokines, whilst reducing the expression of pro-inflammatory cytokines [34,124,125]. Since EPI-NCSCs can easily be transduced to overexpress GFP [126], genetic manipulations to elevate neurotrophic factor expression seems feasible, and with this review we hope to prompt further studies investigating the beneficial characteristics of those cells.…”
Section: Epidermal Neural Crest Stem Cells As a Promising Candidate Imentioning
confidence: 98%
“…Based on the above presented studies, BM-MSCs and neural stem cells are the most abundantly used cell-types that can be genetically modified to enhance their potential when transplanted in animal models of stroke. However, our investigations revealed that epidermal neural crest stem cells (EPI-NCSCs) can also benefit the inhospitable context of rat model of ischemic stroke [34] as well as ex vivo [114] and in vivo [115] models of spinal cord injury. EPI-NCSCs are located in the bulge area of the hair follicle, and retain the differentiation potential of their neural crest origin, so that they can differentiate into neural lineages [116].…”
Section: Epidermal Neural Crest Stem Cells As a Promising Candidate Imentioning
confidence: 99%
See 2 more Smart Citations
“…In cerebral ischemia, EPI-NCSCs and BM-MSCs show equal therapeutic potential [ 7 ]. In animal models of peripheral nerve injury [ 8 ] and stroke [ 7 ], EPI-NCSCs showed superior immunomodulation properties. Furthermore, EPI-NCSCs demonstrated their curative abilities in Alzheimer’s disease, and in vivo as well as ex vivo models of spinal cord injury.…”
mentioning
confidence: 99%